The Development Trend of Chinese History Studies in the United States from Philip C. C. Huang’s Theory - Jiang, Jie (Journal of Humanities and Social Sciences Studies, 2023)
The development of Chinese history research in the United States has undergone a transformation from a "Western-centered view" to a "China-centered view". In this new era, scholars of Chinese history call for a new change in research methods. Philip C.C.Huang, a Chinese-American, puts forward the "crisis of normative understanding" and the "four traps" in the study of modern Chinese history. The purpose of this paper is to analyze the breakthrough of Philip C.C.Huang’s theory of Chinese history research on the original model and its promotion of Chinese history research in the United States. Starting from Philip C.C.Huang’s study of Chinese history, the article analyzes the transcendence of his theory to the previous dichotomy and tries to summarize the development trend of Chinese history research in the United States. It is found that Philip C.C.Huang’s theory transcends the dichotomy of Chinese and Western concepts and breaks through the limitations of both theoretical and empirical research, and his Chinese-American identity as a "marginalized person" also provides evidence of the authenticity and objectivity of his theory, which, however, still needs to be further improved. This study identifies the core ideas and shortcomings of Huang’s theory and helps to promote a more scientific and convincing study of American Chinese history.